Prices Marketing Strategies: An Overview: Exploring Pricing Objectives in Marketing Strategies (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Pricing is one of the major elements of the marketing plan. It enables to differentiate a product or service from another one of similar characteristics. Pricing decisions derive from the underlying objectives and best-suited strategies. The elements of pricing objective include profit maximization, revenue maximization, quality leadership, quantity maximization and survival Pricing objective is focused on three factors, i.e. nature, the desired level of attainment and the associated time horizon. Pricing objectives of service organizations are profit maximization, sales maximization, market share maximization, market share increase, return on investment (ROI), price differentiation, price stability in the market.